Androgen receptor (CAG)n repeat polymorphism contributes to risk of sudden cardiac death originated from coronary artery disease with sex discrepancy. (February 2023) - Zhen, Xiaoyuan; Zhao, Wenfeng; Wang, Jiawen; Li, Lijuan; He, Yan; Zhang, Jianhua; Li, Chengtao; Zhang, Suhua; Luo, Bin; Huang, Jiang; Gao, Yuzhen
Abstract: Sudden cardiac death (SCD) is the leading cause of natural death worldwide which is responsible for almost half of all heart disease deaths, making it a substantial public health problem. Previous epidemiological studies from different countries have demonstrated the significant SCD incident difference rate between males and females. Besides environmental and social effects, differential genetic architecture also underlines the SCD incidence discrepancy. To this end, the functional (CAG)n repeat polymorphism within Androgen Receptor ( AR ) gene was analyzed to evaluate its associations with SCD originated from coronary artery disease (SCD-CAD) susceptibility in Chinese populations using 182 SCD-CAD cases and 564 healthy controls. At allelic level, the (CAG)26 allele conferred a lower SCD-CAD risk in males (adjusted odds ratio [OR] = 0.428; 95% confidence interval [CI] = 0.254, 0.915; P = 0.023). On the contrary, the (CAG)26 allele was reversely associated with a higher SCD-CAD risk in females (OR = 2.581; 95% CI = 0.944, 7.056; P = 0.057). Further cutoff strategy analysis revealed that those male subjects carrying shorter allele (≤26 repeats) had significantly lower SCD-CAD risk (OR = 0.343; 95% CI = 0.221, 0.531; P = 8.1653e −7 ). Additionally, an allele-dependent SCD risk tendency was observed in male subjects. Specifically, compared with males carrying allele longer than 26 repeats, the SCD-CAD risk (OR value) for male subjects carrying shorter alleles (from 25 to 21) gradually increased from 0.437 to 0.533, indicating the (CAG)26 allele of the repeat polymorphism may be the watershed in male SCD etiology. Lastly, the length variations associated with multiple phenotypes were also summarized. Collectively, our results revealed for the first time that the (CAG)n repeat polymorphism within the AR gene was associated with SCD-CAD risk in Chinese populations with sex discrepancy, proposing a new candidate genetic marker for molecular diagnosis of SCD-CAD. Furthermore, a sex-dependent SCD-CAD risk stratification and prevention approach was encouraged. Further studies with more female samples were warranted to validate our findings. Highlights: ● The (CAG)n repeat polymorphism within the AR gene was associated with SCD-CAD risk. ● A sex discrepancy was observed in the association of the polymorphism and SCD-CAD risk. ● The (CAG)26 allele of the polymorphism may be the watershed in male SCD-CAD etiology. ● A sex-dependent SCD-CAD risk stratification and prevention approach was encouraged.